To Study Vitamin D, Uric acid along with C-REACTIVE Protein in patients of psoriasis in tertiary care hospital in Bihar - Kumar, Rajeev; Raju, Parmanand; Singh, Pawan Pratap; Sinha, Rajesh; Kumari, Rekha (Student’s Journal of Health Research Africa, 2025)
Background Psoriasis, a persistent severe skin disorder mediated by the immune system, affects two to three percent of individuals globally and is becoming recognized as a systemic disease. Emerging evidence suggests that vitamin D deficiency, hyperuricemia, and elevated C-reactive protein (CRP) may contribute to its pathogenesis and associated comorbidities. Despite India’s high prevalence of vitamin D deficiency, studies exploring the interplay of these biomarkers in psoriasis are limited. Methodology A prospective case-control study was conducted in IGIMS, Patna. from February 2020 to October 2021. Out of the 150 participants, 75 had chronic plaque psoriasis and the remaining 75 were healthy controls who were assigned for sex and age. Serum 25-hydroxyvitamin D [25(OH)D], uric acid, along with CRP was measured by chemiluminescent microparticle immunoassay, uricase–peroxidase enzymatic method, and latex-enhanced turbidimetric immunoassay, respectively. The statistical analyses included the t-test, the chi-square test, and Pearson’s correlation; a p-value of less than 0.05 was taken to be significant. Results Psoriasis patients showed markedly reduced serum vitamin D levels compared to healthy controls. In contrast, the patient group’s levels of uric acid and C-reactive protein (CRP) were noticeably higher. All individuals with psoriasis were vitamin D deficient, and nearly half had elevated CRP levels. Vitamin D demonstrated a strong inverse relationship with CRP and a moderate negative association with uric acid, while CRP positively correlated with uric acid. Conclusion Vitamin D deficiency is significantly linked to psoriasis, systemic inflammation, and hyperuricemia, reflecting its systemic nature rather than a skin-limited disorder. Recommendation Routine screening of vitamin D, CRP, and uric acid levels should be integrated into psoriasis management, particularly in regions with endemic vitamin D deficiency. Vitamin D supplementation and metabolic risk monitoring may improve clinical outcomes and reduce long-term comorbidities. Further longitudinal and interventional studies are warranted to establish causality and therapeutic benefits.